Penguatan Kapasitas Kelompok Peternak Kambing Peranakan Ettawa (PE) di Desa Segala Anyar Kecamatan Pujut Kabupaten Lombok Tengah - I Gusti Lanang Media; Moh. Taqiuddin; Maya Nachida; Anwar Fachry; Muh. Prasetyo Nugroho (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Initially, goat farmers in the village of Segala Anyar, sub-district of Pujut, district of Central raised goats individually as in the general model of goat farming in rural areas. Then, the goat has been kept in groups since the government introduced the Peranakan Ettawa (PE) goat with a dual purpose in 2012. However, the progression of goat-farmers groups tends to be slow and their existence in supporting goat productivity improvement is less effective. This community service aims to provide knowledge and understanding to goat-farmer groups regarding: organizational development, collaboration, leadership, and communication. In addition, this activity is also directed to provide assistance in designing a model for developing institutional management of local potential livestock resources. It is expected that targeted-goat farmers will have knowledge and understanding about key aspects in strengthening group capacity towards optimizing institutional roles. Problem-solving was identified by a participatory approach by involving goat farmers intensively, especially recognizing their potential and the problems encountered. The extension methods that have been implemented are lectures, interactive-constructive discussions, and preparation of a 'potential-problem analysis' matrix. After in-class, group monitoring and assistance through field visits were carried out routinely and periodically. The results of this community service are goat farmers gain additional knowledge and understanding about important aspects in order to increase the capacity of their group as well as they already have routine activities, such as regular meetings, strengthening awig-awig, and cooperation with other parties (especially the Faculty of Animal Husbandry, University of Mataram) to strengthen their group.